Music Does Not Facilitate Lexical Tone Normalization: A Speech-Specific Perceptual Process - Tao, Ran; Zhang, Kaile; Peng, Gang (Frontiers in Psychology, 2021)
Listeners utilize the immediate contexts to efficiently normalize variable vocal stream into standard phonology units. However, researchers debated whether nonspeech contexts can also serve as valid clues for speech normalization. Supporters of the two sides proposed a general-auditory hypothesis and a speech-specific hypothesis to explain the underlying mechanisms. A possible confounding factor of this inconsistency is the listeners’ perceptual familiarity of the contexts, as the nonspeech contexts were perceptually unfamiliar to listeners. In this study, we examined this confounding factor by recruiting a group of native Cantonese speakers with sufficient musical training experience and a control group with minimal musical training. Participants performed lexical tone judgement tasks in three contextual conditions, i.e., speech, nonspeech, and music context condition. Both groups were familiar with the speech context and not familiar with nonspeech context. The musician group was more familiar with the music context than nonmusician group. The results evidenced the lexical tone normalization process in speech context but not nonspeech nor music contexts. More importantly, musicians did not outperform nonmusicians on any contextual conditions. The findings showed that even high familiarity with a non-linguistic context cannot elicit an effective lexical tone normalization process, supporting the speech-specific basis of perceptual normalization process.